THU0403 AXIAL SPONDYLOARTHRITIS INDUCES MUSCLE DISFUNCTION, THE ROLE OF BODY COMPOSITION PARAMETERS: MYOSPA STUDY. (June 2019) - Sequeira, Maria Luisa; Santos, Inês Da Costa; Amador, Rita; Domingues, Lucia; Crespo, Carolina; Rodrigues-Manica, Santiago; Ramiro, Sofia; Sepriano, Alexandre; Teixeira, Diana; Neto, Agna; Torres, Rita Pinheiro; Calhau, Conceição; et al.
Abstract : Background: Sarcopenia as well as abnormalities in body composition are common features in several chronic diseases and have been shown to lead to increased morbidity and mortality. However, their assessment in young patients with axial spondyloarthritis (axSpA) has not been performed thus far. Objectives: To assess the skeletal muscle mass, strength and performance as well as body composition in patients with axSpA compared to healthy controls. Methods: Patients between 18 and 50 years of age with the diagnosis of axSpA and short disease duration (under 10 years) and classified according to the ASAS criteria were included. Healthy individuals matched by gender and age (1:1) were used as control group. Muscle strength (MS) was assessed by resisted flexion of the dominant forearm using a hand dynamometer. Muscle performance was assessed with the 60 second sit-to-stand test (STS60) and with 5 times sit-to-stand test (STS5). Body composition was assessed with octapolar multifrequency bioelectrical impedance analysis (InBody 770). The level of physical activity was measured by the IPAQ questionnaire. BASDAI and BASFI were used to evaluated disease activity and function, respectively. All measures (except age and disease duration) are reported as median and 25 th and 75 th percentiles. Non-parametric tests were used to compare groups. Results: A total of 27 patients and 27 controls were included [mean age (36.5 ± SD 1.0), 66% males]. AxSpA patients had symptom duration of 7.0 ± SD 0.9 years, BASDAI 2.7 (1.4-3.6) and BASFI 0.9 (0.3-3.2). Compared to controls, axSpA patients had less MS in the dominant upper limb (DUL) (46.0 (37.5-70.6) vs 71.2 (54.1-83.4) kg, p=0.006) and worse performance on the STS60 test (48.0 (27.5-64.3) vs 63.0 (53.0-68.0) repetitions, p=0.010). These differences were maintained after normalization for lean mass (LM) (MS_DUL/LM_DUL and STS60/Total_LM). In addition, compared to controls, axSpA patients had higher body fat (BF) (19.8 (12.1-29.1) vs 15.7 (10.1-22.2) kg, p=0.041), torso fat (TF) (10.3 (6.3-15.9) vs 8.1 (5.1-11.1) kg, p=0.450) and visceral fat (VF) (87.3 (52.7-145.1) vs 65.4 (41.8-96.4) cm 2, p=0.034). No differences were registered for weight, body mass index, total body water, extracellular water, fat free mass, LM and bone mineral content between groups. The level of physical activity, measured by the IPAQ questionnaire, was identical between patients and healthy controls (p=0.500). Conclusion: Compared to healthy controls, young axSpA patients have a reduction in muscle strength and muscle performance with maintenance of muscle mass and levels of physical activity. These preliminary results underline the relevance of further investigations. *Values are median (IQR) unless otherwise indicated. Comparison between patients and controls tested by paired samples t -test unless otherwise indicated. §Comparison between patients and controls tested by Chi-Square test in Gender and Physical Activity variables. Disclosure of Interests: Maria Luisa Sequeira: None declared, Inês da Costa Santos: None declared, Rita Amador: None declared, Lucia Domingues: None declared, Carolina Crespo: None declared, Santiago Rodrigues-Manica Grant/research support from: Novartis, MSD, Speakers bureau: Novartis, Sofia Ramiro Grant/research support from: MSD, Consultant for: AbbVie, Lilly, MSD, Novartis, Pfizer, Sanofi, Speakers bureau: AbbVie, Lilly, MSD, Novartis, Pfizer, Sanofi, Alexandre Sepriano: None declared, Diana Teixeira: None declared, Agna Neto: None declared, Rita Pinheiro Torres: None declared, Conceição Calhau: None declared, Jaime Branco: None declared, Fernando Pimentel dos Santos Grant/research support from: From Abbvie and Novartis, Speakers bureau: Abbvie, Novartis, Pfizer, Biogen,